2011
DOI: 10.1002/hipo.20918
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic modulation of sharp wave‐ripple activity in rat hippocampal slices

Abstract: Norepinephrine (NE) has been shown to facilitate learning and memory by modulating synaptic plasticity in the hippocampus in vivo. During memory consolidation, transiently stored information is transferred from the hippocampus into the cortical mantle. This process is believed to depend on the generation of sharp wave-ripple complexes (SPW-Rs), during which previously stored information might be replayed. Here, we used rat hippocampal slices to investigate neuromodulatory effects of NE on SPW-Rs, induced by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 52 publications
1
35
0
Order By: Relevance
“…This in turn will support cAMP-dependent processes underlying LTP and may enable strengthening of weak plasticity. In line with this, it has been reported that β-adrenergic receptor activation enhances CA3 network activity by increasing CA3 burst activity (Jurgens et al, 2005) and facilitates the induction of LTP and sharp-wave ripples (Ul Haq et al, 2011). Under conditions where LTP is induced solely by electrical stimulation of afferent fibers, the LTP that is induced is already “strong.” This induction of very potent and persistent LTP may thus circumvent the need for support through the noradrenergic system and enable cAMP-dependent pathways to be recruited by the stronger activation of glutamatergic receptors or by other neuromodulatory systems.…”
Section: Discussionmentioning
confidence: 63%
“…This in turn will support cAMP-dependent processes underlying LTP and may enable strengthening of weak plasticity. In line with this, it has been reported that β-adrenergic receptor activation enhances CA3 network activity by increasing CA3 burst activity (Jurgens et al, 2005) and facilitates the induction of LTP and sharp-wave ripples (Ul Haq et al, 2011). Under conditions where LTP is induced solely by electrical stimulation of afferent fibers, the LTP that is induced is already “strong.” This induction of very potent and persistent LTP may thus circumvent the need for support through the noradrenergic system and enable cAMP-dependent pathways to be recruited by the stronger activation of glutamatergic receptors or by other neuromodulatory systems.…”
Section: Discussionmentioning
confidence: 63%
“…In-vitro recordings were performed in stratum pyramidale of area CA1 and occasionally also in area CA3 using an interface chamber and extracellular glass electrodes (filled with 154 mM NaCl, tip diameter 2-3 μM, resistance 2 to 4 MΩ) as previously reported (Hamon, Stanton, and Heinemann 1987; Ul haq et al 2011). Brief (100 μs) electrical pulses were applied using 25 μm bipolar platinum electrodes (ca.…”
Section: Methodsmentioning
confidence: 99%
“…Evoked signals were obtained using 50 % of the intensity required to induce maximal responses. Two protocols were used for recurrent repetitive stimulation: 10 trains of 10 stimuli each with an inter-train interval of 1 s, or 3 trains of 40 stimuli each with an inter-train interval of 40 s (Wöhrl et al 2007a; Ul haq et al 2011). Stimulation frequencies were between 1 and 100 Hz (to stratum radiatum) or 20 or 200 Hz (stratum lacunosum moleculare).…”
Section: Methodsmentioning
confidence: 99%
“…NE was further reported to be involved in facilitation of LTP induction—an effect that is mediated by ß receptors of NE involving also facilitated activation of N-methyl-D-aspartate (NMDA) receptors. Interestingly, ßreceptor agonists of NE facilitated induction not only of LTP but also of SPW-R complexes (Ul Haq et al, 2012). When testing for effects of NE alone, LTP was induced but SPW-R did not appear.…”
Section: Role Of Neuromodulators On Theta Gamma Oscillations Sharp mentioning
confidence: 99%
“…This indicates that during induction of LTP certain synapses increase coupling efficacy but are not yet ready to integrate their activity into a neuronal ensemble. NE blocked stimulation induced SPW-R through activation of alpha-1 receptors for NE (Ul Haq et al, 2012). The underlying mechanism seems to be related to an alteration in presynaptic release probability mediated by effects on transmitter release.…”
Section: Role Of Neuromodulators On Theta Gamma Oscillations Sharp mentioning
confidence: 99%